Concepts of "Decentralization" and "Federalization" in Ukraine: Political Signifiers or Distinct Constitutionalist Approaches for Devolutionary Federalism?. Issue 3 (2nd July 2016) - Marlin, Marguerite
Abstract : While the implementation of decentralization in Ukraine holds promise for improving the weak state of consociationalism there, the framing of the issue along regionally distinct lines persists. After a discussion of how preferences for "decentralization" over "federalization" have been inspired in Ukraine, the article evaluates the significance of these terms beyond sociopolitical stratification, that is, their relevance for constitutional reform of unitary states. Belgium and Spain, two countries that transitioned from unitary states to federal and decentralized systems (respectively) are viewed as instructive cases here. Overall, it is found that either approach abets successful devolutionary federalism if accompanied by ongoing, underlying measures to improve consociationalism.